Electoral Violence in Africa: An Analysis of Factors, Dimensions, Effects and Mitigating Factors - Tacham, Follah Placate; Acho, Mannjong Callistus (International Journal of Social Science Research, 2024)
Elections are key elements of democratic processes. This article aims at providing reasons for election-related violence in Africa, their dimensions, effects, and mitigating factors. Elections are supposed to provide for a transparent and peaceful change of government, the distribution of power, and the promotion of democracy, but most elections in Africa are characterized by violence at various stages of the process. In war-torn countries and even in some stable African countries, incumbents are often manipulating or believed to be tampering with the electoral processes. The opposition parties also have incentives to further their strength through the use of violence. Such violence is potentially damaging democratic processes and undermining progress towards democratization. Electoral violence has varied causes, as highlighted in this article. Beyond direct effects such as hindering people from casting their vote and preventing candidates from participating in the electoral process, electoral violence can have long-term effects. Thus, managing election-related violence would build a strong, democratic, and peaceful society based on the rule of law, accountability, and transparency. Various strategies are used by different actors to achieve this. This article uses a qualitative research design. Information on the research is gathered purely from the review of scholarly articles and reports on the topic. The information presented is based on a synthesis of findings from these sources. From the synthesis of information from other reviews, we have in this article gathered and presented the main causes, effects, dimensions, and some mitigating factors of electoral violence in Africa